Modeling Educational Service Quality and Parental Word of Mouth Intention in Early Childhood Education - Regina Melvin; Ronald Suryaputra; Dany Moenindyah Handarini (Al-Qalam Institue, 2026)
This study aims to examine the influence of Educational Service Quality on Parents’ Word of Mouth (WOM) Intention through Parental Satisfaction in Early Childhood Education. Educational service quality is conceptualized as a second-order construct formed by the five SERVQUAL dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. A quantitative explanatory design was employed using a survey method involving parents of children enrolled in a private early childhood education institution in Surabaya, Indonesia. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results reveal that Educational Service Quality has a strong positive effect on Parental Satisfaction, which in turn significantly influences Parents’ WOM Intention. Mediation analysis confirms that Parental Satisfaction serves as a significant intervening variable in transmitting the effect of service quality on WOM intention. At the dimensional level, Reliability and Responsiveness emerge as the strongest contributors to perceived service quality. These findings imply that early childhood education institutions should prioritize satisfaction-oriented service management by strengthening reliable administrative systems and responsive communication practices to enhance parental advocacy, institutional legitimacy, and sustainable competitiveness.